Plasma (1→3)‐β‐D‐glucan assay and immunohistochemical staining of (1→3)‐β‐D‐glucan in the fungal cell walls using a novel horseshoe crab protein (T‐GBP) that specifically binds to (1→3)‐β‐D‐glucan - Tamura, Hiroshi (J Clin Lab Anal, 1998)
A highly sensitive enzyme‐linked immunosorbent assay specific to (1→3)‐β‐D‐glucans (GBP‐ELISA) has been developed using a novel (1→3)‐β‐D‐glucan‐binding protein (T‐GBP), which was purified from the amebocyte lysate of the Japanese horseshoe crab, Tachypleus tridentatus. This method allowed quantitation of the glucans in a concentration range of 0.1–1,000 ng/ml, regardless of linear and branched structures, and was applied to determine the amounts of (1→3)‐β‐D‐glucan in human and animal plasmas for diagnosis of fungemia. High levels of plasma glucan contents in clinical samples were found to be correlated closely with the severity of fungal infection. T‐GBP was successfully utilized for indirect immunofluorescence staining of (1→3)‐β‐D‐glucan in Candida albicans cell walls. J. Clin. Lab. Anal. 11:104–109. © 1997 Wiley‐Liss, Inc.